Dissolved nitrogen in a tropical river-sea continuum: a seasonal view on the distribution and transformation - Longyun Lai; Moritz Müller; Rahayu Sukmaria Sukri; Changi Wong; Aazani Mujahid; Sumei Liu; Zhaomeng Xu; Tim Rixen; Thorsten Warneke; Justus Notholt; Shan Jiang (Deep Sea Research Part II: Topical Studies in Oceanography, 2026)

Environmental conditions and carbonate chemistry variability influencing coral reef composition along the Pacific coast of Costa Rica - Celeste Sánchez-Noguera; Ines D. Lange; Jorge Cortés; Carlos Jiménez; Christian Wild; Tim Rixen (Frontiers in Marine Science, 2025)
Coral reef development is influenced by a wide variety of factors, including temperature, salinity, nutrient concentrations, and carbonate chemistry. Studies focusing on physicochemical drivers of coral reef distribution and composition in the Eastern Tropical Pacific (ETP) are scarce, and carbonate chemistry and nutrient data for this region are limited. This study measured coral reef composition and physicochemical parameters along the Pacific coast of Costa Rica, over a one-year period at three locations: Santa Elena and Matapalo in the north, and Parque Nacional Marino Ballena in the south. Our results show high seasonal and spatial variability of physicochemical conditions with significant differences mainly explained by inorganic nutrient concentrations, with driving processes also having a strong influence on the variability of carbonate chemistry parameters. Coastal upwelling is the main driver of the seasonal variability in Santa Elena. Comparison of seasonal dissimilarity within locations confirms the presence of a geographical gradient, with stronger influence of the upwelling in Santa Elena relative to Matapalo, where several parameters displayed a lower seasonality and a carbonate system that supports reef development throughout the year. Conversely, in Marino Ballena the river discharges during rainy season exerted a strong control on the seasonal variability. The integrated analysis of coral reef composition and physicochemical parameters suggests that in addition to inorganic nutrients carbonate chemistry also plays a key role in coral distribution. Analyzing the spatial distribution of the main reef builders provides insights into the species-specific tolerance to varying conditions. Pavona clavus is widely distributed in both the northern and southern locations, suggesting that this massive coral is very tolerant to the high variability of physicochemical conditions. The dominant corals in the north ( Pavona gigantea and Pocillopora spp.) are highly tolerant to nutrient-enriched cold waters with low aragonite saturation, while one of the main reef-builders in southern locations ( Porites cf. lobata ) cope better with low salinity, low aragonite saturation and low light intensity caused by river discharges. Understanding the preferences of individual coral species at our study locations can shed light on the environmental factors driving coral reef distribution in other locations of the ETP.

Simulating potential impacts of bottom trawling on the biological carbon pump: a case study in the Benguela Upwelling System - Claire Siddiqui; Tim Rixen; Niko Lahajnar; Tarron Lamont; Anja K. van der Plas (Frontiers in Marine Science, 2024)
Bottom-trawl fishery is known to cause major disturbances to marine sediments as the dragging of trawl gears across the seabed fosters sediment resuspension, which can lead to organic particle remineralization and release of benthic CO 2 and nutrients into bottom waters. However, its effects on carbon cycling and biological productivity, especially in highly productive regions like the Benguela Upwelling System (BUS), are less well studied. Here, we simulated carbon (C) and nutrient pathways from the trawled coastal seabed to overlying water masses that are being upwelled into the sunlit surface within the BUS, using shipboard data on sea surface and water column characteristics and published benthic CO 2 emission estimates from bottom-trawled sediments. The latter reports 4.35 and 0.64 Tg C year -1 to be released from the seabed into upwelling source waters after bottom trawling in the northern (NBUS) and southern (SBUS) subsystems, respectively. Based on these values, we estimated a corresponding nitrate (N) input of 1.39 and 0.47 µmol kg -1 year -1 , enhancing source water nitrate concentrations by ~5% and ~2%. Trawl-induced nitrate input into the sunlit surface could support a new production of 3.14 and 0.47 Tg C year -1 in the NBUS and SBUS, respectively, recapturing only 2/3 of CO 2 released after bottom trawling into biomass, mainly due to differences in stoichiometric C:N ratios between the sediment (~9) and surface biomass (Redfield, 6.6). The remaining benthic CO 2 can thereby lead to an increase in surface CO 2 concentration and its partial pressure (pCO 2 ), impeding CO 2 uptake of the biological carbon pump in the BUS by 1.3 Tg C year -1 , of which 1 Tg C year -1 is emitted to the atmosphere across the northern subsystem. Our results demonstrate the extent to which bottom trawling may affect the CO 2 storage potential of coastal sediments on a basin-wide level, highlighting the need to better resolve small-scale sediment characteristics and C:N ratios to refine trawl-induced benthic carbon and nutrient effluxes within the BUS.

Greenhouse gas concentrations and emissions from a plastic-lined shrimp pond on Hainan, China - Tim Rixen; Marco Drews; Hella van Asperen; Wang Daoru; Alexandra Klemme; Thorsten Warneke (Estuarine, Coastal and Shelf Science, 2023)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Oxygen and Nutrient Trapping in the Southern Benguela Upwelling System - Tim Rixen; Niko Lahajnar; Tarron Lamont; Rolf Koppelmann; Bettina Martin; Justus E. E. van Beusekom; Claire Siddiqui; Keshnee Pillay; Luisa Meiritz (Frontiers in Marine Science, 2021)
The Benguela Upwelling System in the southeast Atlantic Ocean is of crucial socio-economic importance due to its high productivity. However, predicting its response to global change and understanding past changes are still great challenges. Here, we compile data obtained from a research cruise and an oceanographic mooring to demonstrate that a topographically steered nutrient trapping zone develops in a narrow belt along the coast during the main upwelling season in austral spring and summer in the southern Benguela Upwelling System. High nutrient concentrations within this zone increase the impact of upwelling on the productivity of the southern Benguela Upwelling System, but the efficient nutrient trapping operates at the expense of decreasing oxygen concentrations. This enhances the probability of anoxic events emerging toward the end of the upwelling season. However, at the end of the upwelling season, the front that separates the coastally trapped waters from open shelf waters weakens or even collapses due to upwelling cessation and the reversing current regime. This, in addition to a stronger vertical mixing caused by winter cooling, fosters the ventilation of the nutrient trapping zone, which reestablishes during the following upwelling season. The postulated intensification of upwelling and changes in the ecosystem structure in response to global warming seem to reduce the nutrient trapping efficiency by increasing offshore advection of surface waters and plankton blooms. The intensified upwelling and resulting lower biological oxygen consumption appears to mask the expected impacts of global warming on the oxygen minimum zone (OMZ) in the southern Benguela Upwelling System. In contrast to other OMZs, including those in northern Benguela Upwelling Systems, the OMZ in the southern Benguela Upwelling System reveals so far no detectable long-term decrease in oxygen. Thus, the nutrient trapping efficiency seems to be a critical feature mitigating global change impacts on the southern Benguela Upwelling System. Since it is topographically steered, regional impacts on the nutrient trapping efficiency appear also to explain varying responses of upwelling systems to global change as the comparison between southern and northern Benguela Upwelling System shows. This emphasizes the need for further and more comparable studies in order to better understand the response of Eastern Boundary Upwelling Systems and their ecosystem services to global change.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

The Spatial and Temporal Variability of Air-Sea CO2 Fluxes and the Effect of Net Coral Reef Calcification in the Indonesian Seas: A Numerical Sensitivity Study - Bernhard Mayer; Tim Rixen; Thomas Pohlmann (Frontiers in Marine Science, 2018)

The impact of Indonesian peatland degradation on downstream marine ecosystems and the global carbon cycle - Jesse F. Abrams; Sönke Hohn; Tim Rixen; Antje Baum; Agostino Merico (Global Change Biology, 2016)
Tropical peatlands are among the most space‐efficient stores of carbon on Earth containing approximately 89 Gt C. Of this, 57 Gt (65%) are stored in Indonesian peatlands. Large‐scale exploitation of land, including deforestation and drainage for the establishment of oil palm plantations, is changing the carbon balance of Indonesian peatlands, turning them from a natural sink to a source via outgassing of CO 2 to the atmosphere and leakage of dissolved organic carbon ( DOC ) into the coastal ocean. The impacts of this perturbation to the coastal environment and at the global scale are largely unknown. Here, we evaluate the downstream effects of released Indonesian peat carbon on coastal ecosystems and on the global carbon cycle. We use a biogeochemical box model in combination with novel and literature observations to investigate the impact of different carbon emission scenarios on the combined ocean–atmosphere system. The release of all carbon stored in the Indonesian peat pool, considered as a worst‐case scenario, will increase atmospheric pCO 2 by 8 ppm to 15 ppm within the next 200 years. The expected impact on the Java Sea ecosystems is most significant on the short term (over a few hundred years) and is characterized by an increase of 3.3% in phytoplankton, 32% in seagrass biomass, and 5% decrease in coral biomass. On the long term, however, the coastal ecosystems will recover to reach near pre‐excursion conditions. Our results suggest that the ultimate fate of the peat carbon is in the deep ocean with 69% of it landing in the deep DIC pool after 1000 years, but the effects on the global ocean carbonate chemistry will be marginal.

Upwelling Increases Net Primary Production of Corals and Reef-Wide Gross Primary Production Along the Pacific Coast of Costa Rica - Ines Stuhldreier; Celeste Sánchez-Noguera; Florian Roth; Jorge Cortés; Tim Rixen; Christian Wild (Frontiers in Marine Science, 2015)